EFFECTIVENESS OF THE E-PAK LADI KIOSK AS A POPULATION ADMINISTRATION SERVICE IN KARANG PLOSO VILLAGE, PASURUAN - Mauludi, Farah Rifki Azmi; Rodiyah, Isnaini (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to evaluate the effectiveness of the E-Pak Ladi Kiosk as an innovation in civil administration services in Karang Ploso Village, Pasuruan Regency. The main focus of the study is to assess the extent to which this service is able to meet the needs of the community in processing civil documents quickly, easily, and efficiently. Method: This study uses a qualitative method with data collection techniques through interviews, observations, and documentation. Data analysis was carried out using Miles and Huberman's interactive model with four stages: data collection, data reduction, data presentation, and drawing conclusions. Results: The results showed that the E-Pak Ladi Kiosk in Karang Ploso Village was quite effective in improving access to population administration services, especially for people who live far from service centers and vulnerable groups such as the elderly. This program can reduce residents' dependence on broker services. However, several obstacles were found, such as a lack of socialization, limited facilities and infrastructure, and technical glitches that still need to be addressed. Novelty: The novelty of this research lies in the evaluation focus on the implementation of digital service innovation at the village level using the effectiveness indicators of Budiani (2007), as well as in providing community-based and digital literacy approach-based recommendations as solutions to strengthen the implementation of technology-based public services in rural areas.